Komodifikasi pada Akun Instagram @lambe_turah dalam Perspektif Ekonomi Politik di New Media - Tri Febri Kurniawan; Raden Aru Suryoprakoso; Sulfa Fitriani Lamunuhia (Sekolah Tinggi Ilmu Komunikasi Indonesia Maju, 2023)
This study aims to analyze the process of commodification of content, audiences, and workers on the @lambe_turah Instagram account. Using Vincent Mosco's commodification theory, the approach used is a qualitative descriptive approach. The results of the study show that there is indirect exploitation and commodification of content, audiences, and workers towards the followers of the Instagram account @lambe_turah. Exploitation and commodification occur smoothly because almost all followers of the @lambe_turah account will voluntarily help spread information in virtual communities on Instagram.